Using expanded polystyrene geofoam and tire-derived aggregate in different forms to reduce vertical earth pressure on high-filled cut-and-cover tunnels. Issue 1 (31st December 2022) - Arkawazi, Shamil Ahmed Flamarz; Hajiazizi, Mohammad
Abstract: Using the high-filled cut-and-cover tunnels (HFCCTs) provides a typical solution for the possibility of using valuable lands with plateaus terrain. Because of the high quantities of backfill soil above the HFCCT, at present, the existing estimating methods of the vertical earth pressure (VEP) may not suit the HFCCTs construction. The ability to estimate the load or pressure on the HFCCTs is essential. As a principle, the soil column pressure equation can be used to estimate VEP on the HFCCTs. This study presents a numerical investigation of the effect of using expanded polystyrene (EPS) and tire-derived aggregate (TDA) in different forms on the relative vertical displacements and VEP reduction on the HFCCTs. The results showed a significant VEP reduction on the HFCCTs, especially with the use of TDA in different forms. Also, a comparison is made between the calculated and estimated VEP values on the top of the HFCCT study model with the base conditions using the soil column pressure equation, Li et al. (2019) modified equation, and Abaqus CAE 2019 software. The calculated and estimated VEP values on the top of the HFCCT study model with the base conditions showed that the calculated value using Li et al.'s (2019) modified equation is 27.942% lower than the calculated value using the soil column pressure equation, which is a high percentage of difference. While the estimated value using Abaqus CAE 2019 is 0.156% higher than the calculated value using the soil column pressure equation, which is a low percentage of difference.